Light and Electron Microscopic Evaluation of Continuous Perineural Levobupivacaine Infusion Effects on Peripheral Nerve and Muscle Tissues in Infant and Adult Rats - Tunalı, Gülden; Akçıl, Eren Fatma; Kaya, Güner; Korkmaz Dilmen, Özlem; Tunalı, Yusuf; Kaya Gök, Ayfer (Cerrahpaşa Medical Journal, 2019)
Objective: Peripheral nerve and muscle damage is one of the risks of continuous peripheral nerve blockade. The aim of this study was to evaluate the tissue histopathological effects of levobupivacaine in infant and adult rats. Methods: This study was performed in 10 infant and 10 adult rats under ketamine anesthesia. A first bolus dose of levobupivacaine followed by 3 h of infusion was applied to the right sciatic nerve area and 0.9% sodium chloride solution was administered to the left sciatic nerve area to both groups. Removal of the sciatic nerve and the muscle tissues was done on the first hour and first week in three rats, respectively, while in the fourth week in the four other rats in both groups. The nerve and muscle tissues were analyzed by light and electron microscopy separately. Results: Light microscopy revealed in all periods various degrees of axonal degeneration and mast cell and epineural cell infiltration in the nerve tissues. Damage was the same between groups. The myonecrosis and inflammatory cell infiltration on muscle tissue were more profound in the levobupivacaine group. More granulation tissue was produced on the fourth week in infant than adult rats. Electron microscopy showed myelin degeneration, edema of myofibrils and mitochondrions, and effacement of cristae in mitochondria. Apoptosis was observed in the muscle tissue of infant rats. Conclusion: There were no differences between the neurotoxic effects of 0.9% sodium chloride and levobupivacaine infusions on either infant or adult rats. In adult rats, myotoxicity caused by levobupivacaine was later healed compared to that by 0.9% sodium chloride infusion and in infant rats, muscle damage was permanent with levobupivacaine. Cite this article as: Tunalı G, Tunalı Y, Kaya Gök A, Korkmaz Dilmen Ö, Akçıl EF, Kaya G. Light and Electron Microscopic Evaluation of Continuous Perineural Levobupivacaine Infusion Effects on Peripheral Nerve and Muscle Tissues in Infant and Adult Rats. Cerrahpasa Med J 2019; 43(2): 50-57.